Assessment of ethnic differences in sunitinib outcome between Caucasian and Asian patients with metastatic renal cell carcinoma: a meta-analysis. (3rd April 2017) - Liu, Xiaoyan; Fiocco, Marta; Swen, Jesse J.; Guchelaar, Henk-Jan
Abstract: Background: An increasing number of studies have reported ethnic differences in sunitinib outcome in metastatic renal cell carcinoma (mRCC) patients. However, a comprehensive analysis is still lacking. Therefore, we systematically collected available published data and performed a meta-analysis to compare sunitinib efficacy and toxicity in Asian and Caucasian mRCC patients. Methods: Data were extracted from published results from clinical trials, expanded access program and real-world clinical practice. Progression-free survival (or time to tumor progression), overall survival, objective response rate and adverse events were used as endpoints to evaluate the differences of sunitinib outcome between the two ethnicities. For adverse events, we focused the following clinically relevant side effects: diarrhea, fatigue, mucositis/stomatitis, hand-foot syndrome, hypertension, leukopenia, neutropenia and thrombocytopenia. Results: A total of 33 publications including 9977 patients were available for meta-analysis. The efficacy of sunitinib in Asian patients was similar to that in Caucasian patients. However, Asian patients showed a higher incidence of all grades toxicity of hand-foot syndrome, > grade 2 fatigue, > grade 2 hand-foot syndrome and > grade 2 thrombocytopenia. Conclusion: Ethnic differences in adverse events of sunitinib in mRCC patients existed and dose adjustment in Asian patients may be considered.